2009
DOI: 10.32725/jab.2009.020
|View full text |Cite
|
Sign up to set email alerts
|

Lithium: a potential estrogen signaling modulator

Abstract: Estrogen replacement therapy (ERT) engenders much debate since several studies contradict its efficacy as a palliative therapy for cognitive decline and neurodegenerative diseases. Signaling transduction pathways alter brain cell activity, survival, and morphology by facilitating transcription factor activation and protein production. The steroidal hormone estrogen and the anti-depressant drug lithium can interact also through these signaling transduction pathways resulting in transcription factor activation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 120 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…Notably, tamoxifen administration at a dose of 5 mg/kg decreased the tissue edema formation and blood brain barrier (BBB) breakdown, glial activation, and neuronal death, caused by total brain irradiation in the adult male Sprague–Dawley rats [ 231 ]. Another ER signaling modulator [ 232 ], lithium, is also reported to reverse radiation-induced cognitive impairment, as Zanni et al [ 223 ] reported. It has been found that lithium treatment promoted hippocampal neurogenesis in C57BL/6J mice, even four weeks after whole-brain radiation (a single dose of 4 Gy).…”
Section: Role Of Selective Estrogen Receptor Modulators In Radiation-...mentioning
confidence: 99%
“…Notably, tamoxifen administration at a dose of 5 mg/kg decreased the tissue edema formation and blood brain barrier (BBB) breakdown, glial activation, and neuronal death, caused by total brain irradiation in the adult male Sprague–Dawley rats [ 231 ]. Another ER signaling modulator [ 232 ], lithium, is also reported to reverse radiation-induced cognitive impairment, as Zanni et al [ 223 ] reported. It has been found that lithium treatment promoted hippocampal neurogenesis in C57BL/6J mice, even four weeks after whole-brain radiation (a single dose of 4 Gy).…”
Section: Role Of Selective Estrogen Receptor Modulators In Radiation-...mentioning
confidence: 99%